Analysis of precipitation datas by Mann Kendall and Sperman's Rho rank correlation statistical approaches in Nevsehir Province of Turkey - BAGDATLI, M. Cüneyt; Can, Esra (Recent Research in Science and Technology, 2019)
In this research, the total and maximum precipitation values of long years (1970-2019) of Nevşehir province, Ürgüp districts and 34 years of Avanos 1986-2019 were subjected to the Mann Kendall and Sperman's Rho rank correlation tests. In this study; Change trends of the precipitation are presented with graphic distrubitions. According to the results of the trend analysis, it has been observed that the average maximum precipitation value for long years in Avanos district, Nevsehir Province and Ürgüp district is 9,1 mm, 11,3 mm, 10,7 mm and average total precipitation is 292,8 mm, 362,9 mm, 326,9 mm respectively. According to the results of maximum precipitation trends, it has been observed that there is a significant increase in Nevşehir province and Ürgüp districts in winter and autumn months. Considering the total precipitation distribution, it is concluded that there is a negative trend in the spring and autumn seasons in Nevşehir province and Ürgüp district.